Mental well-being and test anxiety among students preparing for the university admission exam during the pandemic - Yatkin, Eleyza; Aral, Neriman; Gunes, Lugen Ceren; Tosun, Selim (Frontiers in Psychology, 2023)
Objective: The present study attempted to explore any potential association between test anxiety and mental well-being among high school students preparing for the university admission exam in times of the pandemic. Methods: The sample of this correlational study consisted of 427 senior high school students in Caycuma district of Zonguldak, Turkey. The data were collected online using a demographic information form, the Warwick-Edinburgh Mental Well-Being Scale, and the Westside Test Anxiety Scale between April - May 2021. Results: Our findings revealed student gender, paternal education, availability of a personal room and computer, and motivation for online classes to be factors associated with test anxiety. Besides, we discovered parental age, maternal education and employment, the device used for online classes, perceived effectiveness of distance education, and motivation for online classes to be linked with mental well-being among students. Conclusion: In a nutshell, several factors were discovered to contribute to test anxiety, including student gender, paternal education, availability of a personal room and computer, and motivation for online classes. The findings also suggested some noteworthy factors influencing students’ mental well-being, such as parental age, maternal education and employment, the device used for online classes, perceived effectiveness of distance education, and motivation for online classes. Finally, we uncovered a significant negative association between the participating students’ test anxiety and mental well-being.